2011
DOI: 10.7763/ijeeee.2011.v1.28
|View full text |Cite
|
Sign up to set email alerts
|

Based on Cloud Computing E-commerce Models and ItsSecurity

Abstract: Abstract-as a new concept, cloud computing has attracted the IT enterprise attention especially the e-commerce enterprise. At present, there is a great problem of environmental costs during the enterprises apply the ecommerce, but with the coming of cloud computing, all of the problem will be solved. Therefore, this article will introduce the concepts, the origins and development trend of cloud computing and on the basis of this issue, analyzing the ecommerce models. On the other hand, from the characteristics… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 0 publications
0
10
0
Order By: Relevance
“…Among the reasons claimed are the flexibility and efficiency that become a must for enterprises to do businesses [3]. Cloud computing refers to computing resources provided by some virtual system on demand, which is done through computer networks [3].…”
Section: Introductionmentioning
confidence: 99%
“…Among the reasons claimed are the flexibility and efficiency that become a must for enterprises to do businesses [3]. Cloud computing refers to computing resources provided by some virtual system on demand, which is done through computer networks [3].…”
Section: Introductionmentioning
confidence: 99%
“…Juncai, S., and Shao, Q., in Based on Cloud Computing Ecommerce Models and Its Security" has analysed various cloud E Commerce model with their security aspects [7]. In this article the problem of environmental cost in case of cloud based E Commerce application has been discussed.…”
Section: Figure Ii: B 2 B E Commerce Modelmentioning
confidence: 99%
“…Juncai and Shao [16] showed that the application of cloud technology in the business field. problem of environmental costs during the enterprises apply the e-commerce.…”
Section: Sun and Yuanmentioning
confidence: 99%